DIGITAL TRANSFORMATION OF THE HANDICRAFTS INDUSTRY IN DELHI/NCR: POST-COVID DYNAMICS AND SALES PERFORMANCE - Nandi, Archita; D. P. Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The COVID-19 pandemic posed severe challenges to the handicrafts industry, compelling many enterprises to explore Information and Communication Technology (ICT) as a means of survival and growth. This study investigates the role of ICT in marketing handicrafts within the Delhi/National Capital Region in the post-pandemic period. Employing a cross-sectional research design, data were collected from 234 artisans and enterprises through a structured questionnaire. The analysis, conducted using reliability tests, descriptive statistics, and multiple regression techniques, focused on the impact of digital marketing, social media, and e-commerce platforms on sales performance. Findings reveal a strong positive relationship between ICT adoption and improved sales outcomes, underscoring the crucial role of digital channels in helping artisans recover and expand their businesses after COVID-19. The study offers valuable insights for artisans, entrepreneurs, marketers, and policymakers on how ICT can be leveraged to enhance market visibility, increase revenue, and ensure long-term sustainability of the handicrafts sector.